Evaluating the sustainability of microsoft teams: Mathematics teachers perspectives in digital learning environments - Tri Ahmad Budi Susilo; Rizki Prasetya; Wahyu Sudrajad; Abd Syakur (Journal of Advanced Sciences and Mathematics Education, 2024)
Background: The rapid adoption of technology in education has transformed the teaching and learning process, shifting from traditional classroom settings to hybrid environments that combine in-person and online learning. Microsoft Teams has become a prominent platform in digital learning, particularly during the pandemic, yet its sustainability in supporting long-term educational goals remains underexplored.Aim: This study aims to evaluate the sustainability of Microsoft Teams in digital learning environments through the perspectives of mathematics teachers in Surabaya.Methods: A quantitative-descriptive analytical approach was adopted. Data were collected via an online questionnaire involving 83 mathematics teachers from the Community of Mathematics Teachers (MGMP) in Surabaya. The survey examined task technology fit (TTF) and the use of Microsoft Teams LMS in teaching practices. Descriptive statistical analysis was performed using SPSS 26 to assess the validity and reliability of the questionnaire.Results: The findings indicate that mathematics teachers generally hold a positive perception of Microsoft Teams sustainability in supporting digital learning. Task technology fit (TTF) significantly influenced teachers views on the platform effectiveness, productivity, and its impact on their teaching performance and students outcomes. However, challenges such as technical issues and varying levels of digital literacy impacted its full potential.Conclusion: The study concludes that incorporating Microsoft Teams as a core component of the education curriculum is vital for its long-term sustainability in digital learning environments. Recommendations include addressing existing challenges to optimize its usage and enhance its role in future educational practices.